1997
DOI: 10.1002/cjce.5450750604
|View full text |Cite
|
Sign up to set email alerts
|

Stirring as foam disruption (SAFD) technique in fermentation processes

Abstract: Foam reduction through stimng was studied in 20 L bioreactors with artificial media and with an actual biotransformation process. For a given stirrer configuration and within a certain range of the broth mass, the foam height was correlated with the broth mass, i.e. the distance between upper stirrer and dispersion surface, and with the superficial gas velocity. Increasing the stirrer speed often resulted in reducing the foam height. A mechanistic model was developed for the Stirring As Foam Disruption (SAFD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 15 publications
4
28
0
Order By: Relevance
“…Hoeks et al [6] demonstrated that for values of v L,dl above a certain critical value, v L,dl,0 , foam is virtually absent and thus foam disruption is complete. Furthermore, it was demonstrated that the SAFD technique works equally well with both artificial media and real fermentation broth and that v L,dl,0 does not depend on the medium [6].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Hoeks et al [6] demonstrated that for values of v L,dl above a certain critical value, v L,dl,0 , foam is virtually absent and thus foam disruption is complete. Furthermore, it was demonstrated that the SAFD technique works equally well with both artificial media and real fermentation broth and that v L,dl,0 does not depend on the medium [6].…”
Section: Introductionmentioning
confidence: 98%
“…This would be easiest by moving the upper impeller closer to the dispersion level of the broth. However, some impellers-particularly hydrofoil impellers-are more effective than others in foam disruption with respect to power draw [3,6,12]. The standard Rushton turbine (ratio of impeller diameter over tank diameter (D/T)=0.33) shows a rather poor performance with regard to SAFD [2].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Both chemical and mechanical methods are available for foam control. Mechanical foam-control is preferable to chemical foam-control because it avoids problems such as the lowering of the mass transfer rate, reaction inhibition, and toxicity; moreover, adverse effects on separation and purification of products occur when foaming is controlled by adding antifoam agents (Yagi and Yoshida, 1974;Andrew, 1982;Koide et al, 1985;Hoeks et al, 1997). Numerous mechanical foam-breakers have been proposed.…”
Section: Introductionmentioning
confidence: 99%